2019
DOI: 10.2196/15314
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care Delivery for HIV Prevention and Treatment in Adolescent Girls and Young Women in Zambia: Protocol for a Cluster-Randomized Controlled Trial

Abstract: BackgroundAmong countries in sub-Saharan Africa, Zambia has one of the highest incidences of HIV. Adolescent girls and young women (AGYW) are a particularly affected group because of their social and economic vulnerability.ObjectiveThe goal of this study is to test a multilevel package of interventions at the community and health system levels in Zambia in order to connect AGYW with a source of regular care, which will in turn allow for sustainable, successful implementation of regular HIV testing and adherenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
(34 reference statements)
0
14
0
Order By: Relevance
“… 4 times during pre-transfer (at 3, 6, 9, and 12 months); 3 times after transfer to adult clinic (at 15, 18 and 21 months) (total 36 months) Face-to-face HCW & Peer Sibinga (2018) [ 66 ] Mindfulness-based stress reduction (MBSR) Group 1) Material related to mindfulness, meditation, yoga, mind-body connection; 2) Experiential practice of mindful meditation; 3) Group discussions focused on problem-solving related to barriers to effective practice. 2-h sessions every week for 8 weeks and one 3-h session in week 9 Face-to-face Trained counsellor (MBSR instructor) Subramanian et al (2019) [ 67 ] Integrated Care Delivery of HIV Prevention and Treatment (SHIELD) Group SHIELD: Educational modules on HIV prevention and treatment, general wellness, SRH, communication skills etc. ; youth clubs.…”
Section: Resultsmentioning
confidence: 99%
“… 4 times during pre-transfer (at 3, 6, 9, and 12 months); 3 times after transfer to adult clinic (at 15, 18 and 21 months) (total 36 months) Face-to-face HCW & Peer Sibinga (2018) [ 66 ] Mindfulness-based stress reduction (MBSR) Group 1) Material related to mindfulness, meditation, yoga, mind-body connection; 2) Experiential practice of mindful meditation; 3) Group discussions focused on problem-solving related to barriers to effective practice. 2-h sessions every week for 8 weeks and one 3-h session in week 9 Face-to-face Trained counsellor (MBSR instructor) Subramanian et al (2019) [ 67 ] Integrated Care Delivery of HIV Prevention and Treatment (SHIELD) Group SHIELD: Educational modules on HIV prevention and treatment, general wellness, SRH, communication skills etc. ; youth clubs.…”
Section: Resultsmentioning
confidence: 99%
“…The HPV vaccination, which is generally not stigmatized as it is usually provided before sexual debut, can serve as an entry-point to provide expanded selection of services to AGYW ( 19 ). Our study highlights the willingness Zambian AGYW have in receiving the HPV vaccination with other HIV services along with the need for AGYW, especially among younger age groups, to have the educational and clinic resources needed for cervical cancer screening and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights the willingness Zambian AGYW have in receiving the HPV vaccination with other HIV services along with the need for AGYW, especially among younger age groups, to have the educational and clinic resources needed for cervical cancer screening and prevention. These self-reported preferences were validated through a pilot test exercise conducted by the study team in which 25 AGYW chose to receive the HPV vaccination and provided positive feedback on the integrated clinic services ( 19 ). Our study found that the lack of knowledge on age eligibility by some AGYW suggests a need to offer these services in AGYW-specific settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa, the Lotto to Link trial is using a conditional lottery incentive to engage men in HIV testing and treatment and achieve viral suppression [49] Similarly, the Zwakala Ndoda trial combines male-focused HIV testing, personalised linkage to care, case management and flexible clinic hours to encourage linkage and engagement in care for men [50]. In Zambia, the SHIELD trial aims to demonstrate the use of peer support within communitybased youth clubs and tailored clinical services for young women and adolescent girls [51]. The VIBRA trial in Lesotho will build on previous evidence from Labhardt et al [15 •• ] and hopes to demonstrate the effectiveness of taskshifting same-day ART and drug refill by village health workers, with the option of adherence reminders and lab result delivery by SMS [52].…”
Section: Looking To the Futurementioning
confidence: 99%